Competências necessárias para atuação do arquiteto como coordenador do processo de projeto de edificações (Estudo de caso) - LIMA, Paulo Gesson Mendes (Universidade Federal do Pará, 2013)
The present study sought to identify the skills required in the process of formation of the Architect, during graduation, having focused on his acting as coordinator of the building design process. The survey used a qualitative methodology with exploratory and descriptive approach, involving data collection through survey. Data were analysed as: resolutions of the MEC and CONFEA/CREA, curricular of the faculties of architecture and urbanism of the metropolitan region of Belém-PA and the perception of students and architects (teachers and professionals) through interviews, having as main result a curriculum proposal for recasting in the formation of the architect and urban planner by including expertise on coordination of the building design process order to meet the needs of professional working in the field. The main result was a proposal for the development of skills that tries to work through knowledge, skills and attitudes related to content, learning experiences and forms of assessment, the best way to effectively contribute to the formation of an architect and urban planner in order to enable these professionals can act as coordinator of the process of building design.